Capital Expenditure Programming and Some Alternative Approaches to Risk - Peterson, D. E.; Laughhunn, D. J. (Management Science, 1971)
This paper investigates the potential reduction in decision-making effort in capital budgeting problems obtainable through the use of measures of risk in addition to variance. Specific measures of risk treated are Baumol's lower confidence limit and the maximum probability of loss. The primary purpose of the paper is to present a methodology which imposes certain “constraining relations” on acceptable investment programs rather than one which appeals to a specific utility function as the basis for ordering choices. In this connection a discussion of several different utility functions is presented, along with an analysis of their usefulness when the probability distributions of net present values for various investment portfolios cannot be taken as known. In addition, some of the logical problems involved in constructing a utility function are examined.